Drop landing peak forces are associated with forces generated during surf-like simulated aerial landings. - Forsyth, J. R.; Riddiford-Harland, D. L.; Whitting, J. W.; Sheppard, J. M.; Steele, J. R. (Journal of Australian Strength and Conditioning, 2018)
Relative peak landing forces from drop-and-stick landing task were highly correlated with relative peak landing forces generated during a surf-like simulated aerial landing.